2010
DOI: 10.1172/jci39222
|View full text |Cite
|
Sign up to set email alerts
|

Low doses of killed parasite in CpG elicit vigorous CD4+ T cell responses against blood-stage malaria in mice

Abstract: Development of a vaccine that targets blood-stage malaria parasites is imperative if we are to sustainably reduce the morbidity and mortality caused by this infection. Such a vaccine should elicit long-lasting immune responses against conserved determinants in the parasite population. Most blood-stage vaccines, however, induce protective antibodies against surface antigens, which tend to be polymorphic. Cell-mediated responses, on the other hand, offer the theoretical advantage of targeting internal antigens t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 50 publications
3
61
0
Order By: Relevance
“…Parasite DNA was detectable in the blood of some of the recipient mice after second transfer and third transfer; however, it seems very unlikely that transferred DNA, per se , was responsible for inducing protection in recipient mice. We previously showed that large numbers of killed parasites (without adjuvant) are unable to induce immunity 26. It thus seems most likely that persisting antigen in the blood of mice, and still within RBCs,11 has induced both a cellular immune response and protection.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite DNA was detectable in the blood of some of the recipient mice after second transfer and third transfer; however, it seems very unlikely that transferred DNA, per se , was responsible for inducing protection in recipient mice. We previously showed that large numbers of killed parasites (without adjuvant) are unable to induce immunity 26. It thus seems most likely that persisting antigen in the blood of mice, and still within RBCs,11 has induced both a cellular immune response and protection.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of malaria-specific IgG in serum P. yoelii 17XL crude parasite Ag was prepared, as described previously (10,24). Briefly, P. yoelii 17XL-infected mouse blood was collected, washed in PBS, and lysed with 0.01% saponin (Sigma-Aldrich) at 37˚C for 20 min.…”
Section: Immunization and Challengementioning
confidence: 99%
“…Because of the failure of subunit malaria vaccines, a variety of whole-malaria parasite vaccines, including infection treatment vaccine (9), killed malaria parasite vaccine (10), and genetically attenuated blood-stage malaria vaccine (11,12), have garnered more attention from researchers in recent years. Evidence has shown that the whole-killed parasite vaccine could induce the host to generate protective immunity against blood-stage malaria parasites in both human and animal models (10,13).…”
mentioning
confidence: 99%
See 2 more Smart Citations